Lorenzo Chiesa, The Not-Two: Logic and God in Lacan - Levchuk, Valeria (Stasis, 2018)
Book review: Lorenzo Chiesa, The Not-Two: Logic and God in Lacan Cambridge, MA: MIT Press, 2016, 251 pp., ISBN 9780262529037